Collagen extraction from aquatic animals - Bakar, Jamilah; Mohamad Razali, Umi Hartina; Mat Hashim, Dzulkifly; Sazili, Awis Qurni (2008)
The present invention relates to the use of fish skin as novel industrial source of collagen. Advantageously,said skin is obtained after the filleting or cutting of fresh fish and frozen immediately after filleting/ cutting, thus guaranteeing a very good quality of the base material, both from the bacteriological standpoint and from the standpoint of the native property of the protein.